VARIATIONS OF SEAWEED FLOUR SUBSTITUTION ON FIBER CONTENT LAVA CAKE SEAWEED FLOUR (Eucheuma Cottonii) - Novita Indriani; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aims to increase the fiber value of the lava cake by substituting seaweed flour (Eucheuma cottonii). The research method was experimental, namely processing lava cake by substituting seaweed flour directly. The design used in this study was a non-factorial Completely Randomized Design (CRD), consisting of 4 treatment levels, namely L0 (control), L1 30% seaweed flour), L2 (50% seaweed flour), L3 (70% flour). The results showed that the lava cake substitution of seaweed flour had a significant effect on the fiber content of the product. The 50% treatment of seaweed flour (L2) was the best treatment with fiber content reaching 13.22%.Keywords:eucheuma cottonii, lava cake, seaweed flour